Image of Infrared Thermography and Rectal Temperature of Ewes During Estrus Given Multinutrient Block Supplementation - Nurkhalijah Solihad Nasution; Ma'ruf Tafsin; Fitra Aji Pamungkas (State Islamic University of Sultan Syarif Kasim Riau, 2023)
The aims of this study was to look at infrared thermography images and rectal temperature of ewes during estrus that were given multinutrient block supplementation. This study used 16 ewes that had given birth at least once, were in healthy condition, and had a normal reproductive cycle. The feed ingredients used are forage, MNB I (basic MNB), MNB II (MNB I added with Moringa leaves), and MNB III (MNB II plus the mineral Zn). The parameters observed were rectal temperature, microclimate temperature conditions, and infrared thermography images taken. The data from the analysis were tested for significance using ANOVA. Providing multinutrient block feed (MNB) supplementation to sheep based on vulva temperature parameters taken from a thermal camera showed a faster estrous response compared to sheep that were not given MNB. From the results of the three types of MNB, there was no significant difference in the duration of estrus symptoms. Infrared thermography can be used to strengthen the determination of the estrus phase in ewes.